O que é, o que é?: um ambiente de co-autoria de jogos educacionais baseados em cartas contextualizadas usando conhecimento de senso comum - Pereira, Eliane Nascimento (Universidade Federal de São Carlos, 2008)
Computer use as a mediating tool in education has been discussed and researched in different areas. The aims are to promote knowledge building, to motivate and to engage students and teachers in it. It also increases their digital literacy. However, several factors should be considered in implementing computers at school, for instance, how to involve teachers so they accept computer to change how they teach. Teachers training program should aim at helping them to include computer in their class activities and also to help them to choose software suitable to pedagogic aims defined in school syllabus. This research fulfills the latter aim concerning developing and evaluating an online system which allows teachers to be co-author of an educational online game. Teachers can contextualize it to students' reality, exploring the transversal themes proposed in the Parameters National Syllabus Standards for primary education, allowing teachers to create, even if partially, a computer tool to promote significant learning or to reinforce concepts presented in class. The content card is an outcome of the use of a filtering process of a semantic net generated from the knowledge base of common sense of the Open Mind Common Sense Brasil (OMCS-Br) project. To accomplish the research aims, a step-by-step guide was developed to help teachers to elaborate of the game content. This online game is a guessing game based on contextualized cards, which request players to discover which is secret word from a specific given topic, using some clues presented to him. This game system was developed according to international usability parameters. Then an evaluation test was conducted to evaluate users' satisfaction (in this case specific teachers and students) when they interacted with the game system. In general it can be considered objectives were fulfilled. First, a game system was developed integrated knowledge base. Second, evaluation test reported teachers satisfaction in being co-author a computer game for their students and students are looking forward to using this computer game as support to pedagogic activities at school.
Keywords: Senso comum; Usabilidade; Jogos educativos; Ambiente de co-autoria de jogos; Ensino aprendizagem; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO